ETHNOMEDICINAL PLANTS USED BY IRULA TRIBES OF MARUTHAMALAI HILLS OF COIMBATORE DISTRICT, WESTERN GHATS, INDIA - S.S. TAMILSELVI; A. VENKATACHALAPATHI; S. PAULSAMY (International Journal of Pharma and Bio Sciences, 2016)
The ethnobotanical information was collected through interviews among local traditional healers of Irulas tribes in Maruthamalai hills of Western Ghats. A total of 163 species of plants distributed in 130 genera belonging to 49 families were identified as commonly used ethnomedicinal plants in the study. Trees were the major life form (30%) used for therapeutic uses and decoction was the commonly used method of medicine preparation (39%). Internal uses were more predominant (63%) than the other mode of applications; the study revealed that both single mode of preparation (61 species) and multiple mode of preparation (102 species) of medicine were common. The information documented regarding the therapeutic uses in the present study will provide basic data for further studies mainly focused on conservation, cultivation and economic welfare of the tribal population.